Leadership, Millenials, And Job Satisfaction - Brand, David; Walker, Scott (IJHCM (International Journal of Human Capital Management), 2022)
Employee turnover is a disruptive and costly phenomenon for organizations. Understanding the causes of turnover and how to mitigate such causes offers a tangible benefit to organizations, especially as it relates to Millennials which are the largest portion of the workforce in 2020. The study herein sought to determine whether Millennial generation employee perceptions of leadership style have an association with job satisfaction for college-educated, full-time employees at a mid-sized professional services firm in the United States. The relationship between perceptions of leadership style and employee job satisfaction were evaluated via a non-experimental quantitative study. The research design was a cross-sectional survey administered to 1,567 participants with 354 usable responses obtained. Data collected via a survey demonstrated there is a statistically significant moderate correlation (rs = .32, p < .01) between perceptions of leadership style and job satisfaction at the scale level and that the relationship is stable regardless of gender, tenure, ethnicity, or age. The findings support previous studies of various generational cohorts and extend the knowledge base specific to a Millennial subgroup. This study extends the body of knowledge related to the Full Range of Leadership Theory and adds information for a specific generational cohort in one industry segment. Implications include opportunities for organizations to implement leadership development programs focused on specific behaviors that will increase employee satisfaction.